Body composition in 98 patients awaiting kidney transplantation - Moreau, Karine; Desseix, Aurélie; Germain, Christine; Barthe, Nicole; Bachelet, Thomas; Morel, Delphine; Merville, Pierre; Couzi, Lionel; Thiebaut, Rodolphe; Chauveau, Philippe (Nutrition (Burbank, Los Angeles County, Calif.), 2014)
Recent data suggest that the nutritional status of patients who are on the waiting list for kidney transplantation, influence outcomes after renal transplantation. Body composition (BC) analysis is rarely included in pretransplant evaluation. The aim of this study was to determine how alteration of the BC of these patients could influence pretransplant and post-transplant care. We compared the BC of French patients on a waiting list for kidney transplantation to a sex- and age-matched healthy, European control population. Patients were included when listed for kidney grafting in a prospective longitudinal study (CORPOS). Biological nutritional parameters, fat free mass (FFM) and fat mass (FM) estimated by dual-energy x-ray absorptiometry (DXA) were assessed on the day of wait-list registration. FFM and FM index (FFMi - FMi) are the ratio of FFM and FM to height squared. Results are expressed as median (range). These indexes were compared with previous study values used as a normal range in nutritional assessment and clinical practice. The study included 28 women and 70 men aged 25.3 to 65.9 y. Body mass index ranged from 16.8 kg/m² to 39.4 kg/m². Compared with controls, FMi was higher in women (10.6 kg/m² [3.7–18.6 kg/m²]) than in men (8.1 kg/m² [3.5–13.3 kg/m²] in M) and FFMi was lower in women (14.3 kg/m² [11.8–21.4 kg/m²]) than in men (17.9 kg/m² [13.9-24.2 kg/m²]) (P < 0.01), reflecting an abnormal distribution of body compartments. All biological parameters were within the normal range. BC abnormalities, which can only be detected with the use of DXA, are present in patients on a kidney transplantation waiting list. Detection of these abnormalities could influence the post-transplantation survey in order to prevent the frequent risk for developing metabolic complications after the procedure.